Cloned endogenous retroviral sequences from human DNA. - Bonner, T I (1982)
We have screened a human DNA library using as probe a chimpanzee sequence that contains homology to the polymerase gene of the endogenous baboon virus. One set of overlapping clones spans about 20 kilobases and contains regions of DNA sequence homology to the gag p30, gag p15, and polymerase genes of Moloney murine leukemia virus. Furthermore, the spacings are the same as in Moloney virus between these sequences and a 480-nucleotide region that has the structural characteristics of a 3' copy of the long terminal repeat sequence. Hybridization of the cloned DNA to restriction digests of human DNA indicates that the human genome contains only two copies closely related to the sequence and approximately equal to 10 less closely related copies. This retroviral sequence appears to have been in its present chromosomal location prior to the divergence of man and chimpanzee because the human and chimpanzee clones have 3--4 kilobases of identical 3' flanking sequence.